2010
DOI: 10.1007/s10695-010-9420-9
|View full text |Cite
|
Sign up to set email alerts
|

The study of some haematological and serum biochemical parameters of juvenile beluga (Huso huso) fed oligofructose

Abstract: A study was conducted to investigate the effects of dietary oligofructose (1, 2 and 3%) on the blood profiles of beluga (Huso huso) juveniles (18.77 ± 0.76 g) compared to fish fed an un-supplemented diet. After 7 weeks of feeding on the experimental diets, haematological parameters, metabolic products (cholesterol, glucose and total protein) and serum enzymes (lactate dehydrogenase, alkaline phosphatase, alanine aminotransferase and aspartate aminotransferase) were measured. Compared to the control group (0% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
84
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 31 publications
15
84
0
1
Order By: Relevance
“…In the present study, serum ALT, AST and ALP levels were not affected by dietary mannan oligosaccharide (p>0.05). This result was in agreement with Ahmdifar et al (2011) and Hoseinifar et al (2011b) who reported that prebiotic inulin and oligofructose had no effects on these enzymes in beluga (Huso huso) serum, respectively. The results of the present study showed that dietary mannan oligosaccharides had no effects on RBC, MCV, MCH and MCHC.…”
Section: Haematology and Biochemistrysupporting
confidence: 92%
“…In the present study, serum ALT, AST and ALP levels were not affected by dietary mannan oligosaccharide (p>0.05). This result was in agreement with Ahmdifar et al (2011) and Hoseinifar et al (2011b) who reported that prebiotic inulin and oligofructose had no effects on these enzymes in beluga (Huso huso) serum, respectively. The results of the present study showed that dietary mannan oligosaccharides had no effects on RBC, MCV, MCH and MCHC.…”
Section: Haematology and Biochemistrysupporting
confidence: 92%
“…Growth enhancement as a result of probiotic and prebiotic administration has been reported in several previous studies on a variety of fish and shellfish species fed dietary prebiotics (Mahious et al 2005;Daniels et al 2010;Hoseinifar et al 2010;Mehrabi et al 2011;Sun et al 2011;Soleimani et al 2012). The results of the present study revealed that the supplementation of LAB to the food of common carp significantly improved SGR.…”
Section: Discussionsupporting
confidence: 81%
“…The mechanism by which glucan enhances innate immune response of fish has not been completely elucidated to date (Ai et al, 2007) but some studies have shown that glucan enhances non-specific immunity through direct activation of macrophages (Ai et al, 2007, Sakai, 1999. Hematological parameters are valuable indicators for monitoring fish health, nutritional status and environmental conditions affecting fish (Hoseinifar et al, 2011b, Cnaani et al, 2004. Our results show that dietary CYG had no remarkable effects on RBC, Htc and Hb levels ( Table 2).…”
Section: Discussionmentioning
confidence: 72%